Global transcriptional modulation and nutritional status of soybean plants following foliar application of zinc borate as a suspension concentrate fertilizer - Eloisa Vendemiatti; Rafael Oliveira Moreira; Gabriel Lasmar dos Reis; Inty Omar Hernandez-De Lira; Eugenia Peña-Yewtukhiw; Franz Walter Rieger Hippler; Luis Omar Torres-Dorante; Kiran Pavuluri; Alex Valentine; Vitor L. Nascimento; Vagner Augusto Benedito (Scientific Reports)
Abstract The management of micronutrients, such as boron (B) and zinc (Zn), is critical for plant growth and crop yields. One method of rapid intervention crop management to mitigate nutritional deficiency is the foliar supply of B and Zn. Our study investigates the effect of foliar-supplied B and Zn availability on the global transcriptional modulation in soybean (Glycine max). The transcriptional response to B was more widespread compared to Zn. RNA-Seq of leaves under different B levels revealed modulated genes with potential roles in nutritional homeostasis and stress response that may be key to controlling B status in the plant. We also identified putative B transporters whose expression levels were significantly affected by B supplementation with foliar fertilization of plants growing under low B conditions. Furthermore, a gene lacking functional annotation (Glyma.03G180300) emerged as a novel potential marker of B status. Two genes (Glyma.16G118000, Glyma.16G199000) were consistently induced by Zn availability, highlighting their potential as biomarkers for assessing its status in soybean plants. This work advances our understanding of nutritional homeostasis in soybean plants and identifies target genes and potential molecular mechanisms involved in nutritional response. Our study informs fertilizer design targeting specific nutrient transporters, thereby enhancing nutrient efficiency in crops.